Hubungan Pengetahuan Ibu Nifas Dengan Pelaksanaan Bounding Attachment Di PMB Rasminkita Ginting Kecamatan Tanjung Morawa Tahun 2022 - Deby Nova Sembiring; Deby Cyntia Yun; Ninsah Mandala Putri Sembiring; Indra Agussamad (Pusat riset dan Inovasi Nasional, 2022)
BACKGROUND: According to afifah (2013), The postpartum period is still a vulnerable period for the survival of new mothers giving birth. Most maternal deaths occur during the postpartum period, so postpartum health services play an important role in efforts to reduce maternal mortality. Postpartum services are health services provided to mothers during the period from 6 hours to 42 days after giving birth. The proportion of health service coverage during the postpartum period decreases over the period of time after giving birth. Births that received complete postpartum health services included KF1 at 81.9%, KF2 at 51.8%, and KF3 at only 32.1%. Considering the importance of bounding attachment between mother and baby and the lack of knowledge regarding this matter, it is important to realize this love. The attraction of affection can be manifested from the fetus that is still in the womb and to strengthen the newborn baby can be done using IMD, the aim of which is very beneficial for changes in the psychology of the mother and baby because affection begins with a mother's touch and hug to her baby when carrying out IMD ( early initiation of breastfeeding). OBJECTIVE: Analyzing the Relationship between Knowledge of Postpartum Mothers and the Implementation of Bounding Attchment at the Rasminkita Ginting Clinic, Tanjung Morawa District in 202. METHOD chi square test p value < 0.05 means H0 is rejected and Ha is accepted, the statistical test results show a significant relationship. RESULTS: There is a relationship between the knowledge of postpartum mothers and the implementation of Bounding Attachment at the Rasminkita Ginting Clinic, Tanjung Morawa District in 2022. Suggestions are given for research and for research sites and for educational institutions regarding Bounding Attachment.